Developing a measure for the appropriateness of prescribing in general practice. Issue 4 (1st August 2003) - Britten, N; Jenkins, L; Barber, N; Bradley, C; Stevenson, F
Abstract : Objective: To explore the feasibility of using a broader definition of the appropriateness of prescribing in general practice by developing ways of measuring this broader definition and by identifying possible relationships between different aspects of appropriateness and patient outcomes. Design: A questionnaire study of patients and general practitioners before and after study consultations, supplemented by data collected from patients' medical records and telephone interviews with patients 1 week later. Setting: General practices in the south of England. Participants: 24 general practitioners and 186 of their consulting patients. Main outcome measures: Unwanted, unnecessary, and pharmacologically inappropriate prescriptions; patients' adherence. Results: Before the consultation 42% of patients said they wanted or expected a prescription for their main problem. Prescriptions were written in two thirds (65%) of study consultations, and 7% of these had not been wanted or expected beforehand. Doctors recorded that one in five prescriptions they wrote were not strictly indicated. Of the 92 independent assessments of these prescriptions, four were judged to be inappropriate and in 19 cases the assessors were uncertain. 41% of prescriptions written were wanted, necessary, and appropriate. Subsequently, 18% of patients for whom a prescription had been written were potentially non-adherent and 25% had worries or concerns about their medication. Conclusion: The attempt to measure appropriateness of prescribing along the three dimensions of patients', prescribers', and pharmacological perspectives is both feasible and likely to yield valuable insights into the nature of general practice prescribing and patients' use of medicines.